Impact of Thermal Processing on the Protein Digestibility of Sardines and Sprats - Ivo Doskocil; Barbora Lampova; Petr Smid; Aneta Kopeć (Foods)
Fish are a valuable source of high-quality protein and essential nutrients, making them an integral component of a healthy diet. However, protein digestibility, influenced by preparation methods, is a critical factor in assessing nutritional quality. This study aimed to evaluate the impact of various thermal processing methods on the protein digestibility of two commonly consumed small pelagic fish species: sardines (Sardina pilchardus) and sprats (Sprattus sprattus). Protein digestibility was assessed using two complementary approaches: total protein digestibility and the Digestible Indispensable Amino Acid Score (DIAAS). Fish samples were subjected to different cooking methods, including boiling, steaming, baking, and frying. All thermal treatments enhanced protein digestibility compared to raw fish. Fried samples exhibited the highest total protein digestibility, with sardines reaching 92.4 ± 4.3% and sprats reaching 89.5 ± 4.4%. DIAAS values corroborated these findings, indicating superior protein quality in fried fish. While frying yielded the highest digestibility scores, steaming and boiling provided a favourable balance between improved protein quality and lower potential health risks, with baking achieving comparable results.